A Fractal Based CSRR Loaded Multi-Band Antenna for Wireless Applications - *P. Manikandan, P. Sivakumar, K. Sai Vamsi Krishna, P. Sumanth, T. Poornesh (International Journal of Advanced Science and Technology, 2020)
In this paper, we proposed an antenna structure which uses fractal technology and Complementary split ring resonator (CSRR) in the ground plane of patch which is used to produce multi-band resonance which can be used for various wireless applications. The resonant frequencies that are generated using this antenna with return loss < -10dB are 2.57 GHz, 3.49 GHz, 5.94 GHz, 7.53 GHz, 8.23 GHz, 9.71 GHz, and 12.58 GHz with return losses –10.7dB, -27.5dB, -18.6dB, -21.6dB, -17.8dB, -35.3dB and -44dB respectively.